Gene silencing of cathepsins B and L using CTV-based, plant-mediated RNAi interferes with ovarial development in Asian citrus psyllid (ACP), Diaphorina citri - Ibanez, Freddy; Vieira Rocha, Sâmara; Dawson, William O.; El-Mohtar, Choaa; Robertson, Cecile; Stelinski, Lukasz L.; Soares-Costa, Andrea (Frontiers in Plant Science, 2023)
Diaphorina citri Kuwayama (Hemiptera: Liviidae) is a vector of the bacteria Candidatus Liberibacter americanus (CLam) and Candidatus Liberibacter asiaticus (CLas), which are phloem-restricted and associated with the most important and destructive worldwide citrus disease, Huanglongbing (HLB). Currently, no cure for HLB has been described. Therefore, measures have focused on reducing D. citri populations. In these insects, cathepsin B (DCcathB) and L (DCcathL) enzymes play an important role in digestion, and are involved in embryogenesis, immune defense, and ecdysis. We used a CTV-based vector to deliver dsRNA (CTV-dsRNA) into Citrus macrophylla plants targeting DCcathB and DCcathL genes in D. citri that fed on the phloem of these CTV-RNAi infected plants. Subsequently, we evaluated expression of DCcathB and DCcathL genes as well as the Vitellogenin (Vg) gene by RT-qPCR in D. citri fed on CTV-dsRNA occurring in plant phloem. Also, we demonstrated a defective phenotype in D. citri females as a result of knockdown of DCcathB and DCcathL genes mediated by CTV-dsRNA. Psyllids that fed on plants treated with the CTV-dsRNA exhibited downregulation of the Vg gene, one of the most important genes associated with embryogenic and female development, which was associated with dsRNA-mediated silencing of the two cathepsin genes. Based on our findings, a CTV-based strategy for delivering RNAi via plants that targets DCcathB and DCcathL genes may represent a suitable avenue for development of dsRNA-based tools to manage D. citri that limits the spread of HLB.